Utilization of the dimensions of learning organization for enhanced hospital performance - Alrashidi, Nojoud Abdullah; Lagura, Grace Ann Lim; Celdran, Ma Christina Bello (Frontiers in Communication, 2023)
Background: The healthcare system of Saudi Arabia has evolved radically into an institution that is adaptive to global change and is abreast with new advances in medical field to meet Saudi Vision 2030. The concept and practice of the dimensions of learning organization could provide a framework to significantly improve organizational performance. This study aims to determine the utilization of the dimensions of learning organization as a basis for enhanced performance at hospitals in Hail, Kingdom of Saudi Arabia (KSA). Method: This cross-sectional study included 117 nurse respondents from various government and private hospitals in the Hail region. Staff nurses were surveyed using the Dimensions of Learning Organization Questionnaire (DLOQ), and supervisors and managers were interviewed. Results: Creation of continuous learning opportunities, team learning and collaboration, and strategic leadership in learning were perceived to be very satisfactorily utilized. Promotion of dialogue and inquiry, systems to capture and share learning, and empowerment and connection of the organization to the community were perceived to be satisfactorily utilized. Furthermore, the dimensions were found to be directly correlated, evidently signifying a strong relationship. Conclusion: Overall, hospitals in the Hail region were found to be learning organizations. The dimensions of learning organization were utilized very satisfactorily, and the culture of learning was strongly embedded in the hospitals’ systems and practices.